If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 3x + 2x + 3y = 0 Combine like terms: 3x + 2x = 5x 5x + 3y = 0 Solving 5x + 3y = 0 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-3y' to each side of the equation. 5x + 3y + -3y = 0 + -3y Combine like terms: 3y + -3y = 0 5x + 0 = 0 + -3y 5x = 0 + -3y Remove the zero: 5x = -3y Divide each side by '5'. x = -0.6y Simplifying x = -0.6y
| 4x+90=3 | | 8x^2+-6x=0 | | 28n^2-172n-168=0 | | 8x-6y=-6 | | 8y-6=22-6y | | 2y=-7+2y | | .11x-9=.04(x-81) | | 10p^2+2p-2= | | 12-3n=-36-6n | | 12-2(t-3)=-8t | | 5y-12= | | -25y+18=-15y-25 | | x^2+16-28=0 | | 5x-0.8=-0.2+3x | | 4x+4=9x | | (7x+5)(3x-8)= | | x+[x+1]=1.10 | | y=-5+2(-2) | | a^2+10ab+25b^2-49=0 | | (x+49)(x+4)=O | | x^2-5x+6.25-14=6.25 | | 1x-2y=10 | | w+9=-7 | | 5-4x=x-1.5 | | 5x-0.8=0.2+3x | | 6y-1y-12= | | =6z-(3z-6)+(7-8z) | | 15=3x-6x-3 | | 6y^2+8y-9y-12= | | X+x+1+x+2=274 | | -36=p-6 | | 3=18x+6x^2 |